2018 IEEE Nuclear Science Symposium and Medical Imaging Conference Proceedings (NSS/MIC) 2018
DOI: 10.1109/nssmic.2018.8824379
|View full text |Cite
|
Sign up to set email alerts
|

Bias Dependence of Total Ionizing Dose Effects on 28-nm Bulk MOSFETs

Abstract: This paper investigates the effects of total ionizing dose up to 1 Grad on 28-nm bulk MOSFETs under different bias conditions during irradiation. The aim is to assess the potential use of this commercial bulk CMOS technology in the future highluminosity Large Hadron Collider at CERN that will require highly improved radiation-tolerant tracking systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This is different from the historical worst-bias case-i.e., the switched-on bias condition V GB = V DD and V DS = 0 [23]. Nevertheless, these two bias conditions induce no big difference in the drain leakage current of our 28-nm bulk MOSFETs [24]. Moreover, in most analog circuits and particularly the analog FE electronics, MOSFETs are biased in saturation with a nonzero V DS except the switches working at a zero V DS .…”
Section: Methodsmentioning
confidence: 95%
“…This is different from the historical worst-bias case-i.e., the switched-on bias condition V GB = V DD and V DS = 0 [23]. Nevertheless, these two bias conditions induce no big difference in the drain leakage current of our 28-nm bulk MOSFETs [24]. Moreover, in most analog circuits and particularly the analog FE electronics, MOSFETs are biased in saturation with a nonzero V DS except the switches working at a zero V DS .…”
Section: Methodsmentioning
confidence: 95%
“…The only difference in the implementation of the discriminator between the two prototypes is the switching circuit. In the current implementation the circuit has been changed to use p-type switches since they have proven to be more radiation resistant [25]. This change may have rise the discriminator pre-OC DC voltage point.…”
Section: Analog Front-end Characterizationmentioning
confidence: 99%
“…For instance, Sun et al [9] investigated that GaN HEMTs which are with Schottky metallic gate structures typically exhibit a small shift after TID irradiation, while GaN HEMTs with MOS gates exhibit additional threshold voltage shift compared to similar devices with Schottky gates because of hole trapped in the gate oxide. Lidow et al [10] have studied the E-mode Schottky gate devices and concluded that the devices exhibited drifts of ∼0.2 V. Ives et al [11] have investigated the commercial radio frequency (RF) D-mode Schottky gate power HEMTs and indicated that the devices exhibited shifts of about 0.15 V. On the other hand, although significant progress has been made in understanding the underlying physics of TID irradiation in the Si MOSFETs [12][13][14][15][16][17][18][19], there is not much work undertaken on the TID effects in the Cascode GaN HEMTs. Chen et al [20] have investigated the high and low dose-rate radiation damage effects of the Cascode structure GaN power devices and found that the threshold voltage of the Cascode device was negatively drifted, having no enhanced low dose rate sensitivity effect.…”
Section: Introductionmentioning
confidence: 99%